Obstacles Facing Civilian Community out Reach through reinforcing the Culture of Human Rights from Principals Perspectives in Gaza Governorates - Ahmed Saleh (My University, 2014)
This study aimed at identifying the obstacles which face the civilian community outreach through reinforcing the culture of human rights from principals perspectives in Gaza governorates, The researcher used the descriptive method to investigate the purposes of this study. The sample of this study، chosen randomly، consisted of (100) male and female principals with percentage weight (11.4) from the origin population. To achieve this، the researcher used a questionnaire consisted of (30) items distributed into three domains (cultural، social and political). The result of the study showed that the total degree of obstacles reached (72.92)، and the political got the highest rank with percentage weight (79.22) then، the social obstacles reached a high rank with percentage weight (71.9) and finally، the cultural obstacles came with a medium degree with (67.64)، in addition، the results showed that there are no statistically significant differences due to gender، years of experience and qualification. The researcher suggested some recommendations as: the necessity of saving the administrative، technical and material abilities which reinforce the civilian community outreach institution to spread the culture of human rights. Also، the researcher recommended the civilian community outreach institution to be far away from the conflict and to coordinate among them to achieve common goals، and to give them wide chances to express about their opinions through different mass media.

هدفت هذه الدراسة التعرف إلى المعوقات التي تواجه مؤسسات المجتمع المدني في تعزيز ثقافة حقوق الإنسان من وجهة نظر المديرين في محافظات غزة، وقد استخدم الباحث المنهج الوصفي التحليلي لتحقيق أغراض الدراسة، وشملت عينة الدراسة (100) مديراً ومديرة اختيرت بطريقة عشوائية، وبنسبة (11.4%) من المجتمع الأصلي، ولتحقيق ذلك استخدم الباحث استبانة مكونة من (30) فقرة موزعة على ثلاثة مجالات هي(الثقافية، الاجتماعية، السياسية)، وتوصلت نتائج الدراسة إلى أن درجة المعوقات الكلية كبيرة بنسبة (72.92%)، واحتلت (المعوقات السياسية) المرتبة الأولى بدرجة كبيرة وبنسبة (79.22%) تليها (المعوقات الاجتماعية) بدرجة كبيرة وبنسبة (71.9%)، وأخيراً (المعوقات الثقافية) بدرجة متوسطة وبنسبة (67.64%)، إضافة إلى ذلك أظهرت النتائج أنه لا توجد فروق ذات دلالة إحصائية تعزى لكل من: متغير النوع وسنوات الخبرة والمؤهل العلمي، وقد أوصى الباحث بعدة توصيات أهمها: ضرورة توفير الإمكانات الإدارية والفنية والمادية التي تشجع مؤسسات المجتمع المدني على نشر ثقافة حقوق الإنسان، كما يجب أن تبتعد مؤسسات المجتمع المدني في نطاق عملها عن الصراع، وأن تنسق بينها من أجل تحقيق أهداف مشتركة، وإعطائها فرصة واسعة للتعبير عن آرائها عبر وسائل الإعلام المختلفة.
المعوقات التي تواجه مؤسسات المجتمع المدني في تعزيز ثقافة حقوق الإنسان من وجهة نظر المديرين في محافظات غزة